Facing the Involvement of Youths in Competitions: Soviet Visions and Adaptations to the Rejuvenation of Elite Sports (Second Half of the 20th Century) - Dufraisse, Sylvain (Frontiers in Sports and Active Living, 2020)
This article focuses on Soviet sports authorities' adaptations to youth involvement in elite sports during the second half of the 20th century during the Cold War. It demonstrates that the quest for performance and success in world competitions meant that sportsmen needed to start training at younger ages. This trend led to the development of a biopolitical expertise on youth sports, that mixed scientific research, artistic and intellectual stances and public policy making. It contributed to determining age requirements and a specific system to intensify preparation while protecting the sportsmen involved. Since the mid-1970's, this system was not well-received within the Soviet Union as well as by the wider world. These youth systems embodied the poor Soviet management of childhood.